Wheat yield progress and stability during the last five decades in Argentina - Curin, Facundo; Otegui, María Elena; Gonzalez, Fernanda Gabriela (Elsevier, 2021)
Improvement of grain yield (GY) at farm level, which is closely related to GY potential, seems to be the main alternative to increase wheat (Triticum aestivum L) production. The aim of current research was to assess the genetic progress of GY potential and associated physiological traits as well as the GY stability under diverse environments of cultivars released to the Argentine market during the last five decades (1971–2011). Ten cultivars, classified into two groups of five according to the time to anthesis in late cycle (LC) and early cycle cultivars (EC), were grown under twelve environments (E1 to E12) in Pergamino, Argentina. The environmental index of GY (average of cultivar’s GY in each environment) ranged from 174 to 602 g m−2. Under potential conditions (E1 to E3, 602 to 548 g m−2), GY improved at 0.74 % per year of release (YOR) (or 4.20 g m−2 per YOR) across all cultivars. The harvest index (HI), particularly in LC, and total biomass produced at physiological maturity (BTPM), associated with crop growth rate during stem elongation (CGRSE) and total biomass produced at anthesis (BTA), particularly in EC, were improved by breeding explaining the GY potential increase. Maximum HI reached 0.46, suggesting it can be further improved in both groups, but pre-anthesis growth should continue increasing in EC, as it seemed to be a yield-limiting trait for these cultivars. Grain number per m−2 (GN) increased by recent breeding in both groups with no change in grain weight (GW). This was a consequence of greater grain number per spike (GNS) in EC, as expected, but higher spike number per m−2 (SN) in LC. Fruiting efficiency (FE, grains g−1 of spike dry weight at anthesis -SDWA-), rather than SDWA, seems to have been improved by recent breeding, turning it a key trait to further increase GN. Finally, modern cultivars out-yielded the old ones in a wide range of environments, suggesting that wide adaptation is a valid breeding strategy for Argentine conditions.